Routes of administration of hormone replacement therapy and cardiovascular effects in postmenopausal women. - Manju, Sharma; Xiao-gang, LI; Lu-hong, LI; Rui-xia, HUANG; Yan, YANG; WEI-hong, JIANG (Journal of General Practice and Emergency Medicine of Nepal, 2014)
Earlier results of observational data showed beneficial effects with hormone therapy in women after menopause but the large clinical trials such as the Women’s Health Initiative (WHI), Heart and Estrogen/progestin Replacement Study (HERS) failed to demonstrate protective cardiovascular effects. However, re-analysis of WHI results recommended that the adverse outcomes maybe influenced by several factors such as age, time of initiation, dose, route of hormone therapy and pre-existing cardiovascular disease. In recent times, the use of hormone therapy in postmenopausal women is still limited to climacteric symptoms, probably due to insufficient data to support its use in chronic conditions such as cardiovascular disease. However, results from The Kronos Early Estrogen Prevention Study (KEEPS), has been expected to provide a definite answer to reduce cardiovascular disease with hormone therapy in postmenopausal women. Based on the results from recent studies, re-analysis of WHI results, and WHI /HERS reports, this article highlights the cardiovascular effects of hormone replacement therapy with different routes of administration in postmenopausal women.